2018
DOI: 10.2109/jcersj2.17256
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and modelling of electrical resistivity by four-terminal method during flash sintering of 3YSZ

Abstract: Flash sintering is a newly developed technique to quickly densify conductive ceramics in the presence of an electric field. At a critical combination of field and temperature, densification takes place in a few seconds. This paper investigates the electrical resistivity during flash sintering of 3YSZ by the four-terminal method in combination with numerical modelling of electrical heating and temperature distributions. Densification rates were similar to those observed previously in specimens rapidly heated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Grasso et al [25] have shown through the use of computational modelling, that the macroscopic temperature distribution in a YSZ dog-bone shape is uniform within the gauge section but heterogeneous in the electrode contacting areas. In contrast with Grasso's work, M. Yoshida and co-workers found that dog-bone-like specimens present an non-homogeneous macroscopic distribution of current density, power dissipation and temperature during stage III of FLASH [26].…”
Section: Introductionmentioning
confidence: 67%
“…Grasso et al [25] have shown through the use of computational modelling, that the macroscopic temperature distribution in a YSZ dog-bone shape is uniform within the gauge section but heterogeneous in the electrode contacting areas. In contrast with Grasso's work, M. Yoshida and co-workers found that dog-bone-like specimens present an non-homogeneous macroscopic distribution of current density, power dissipation and temperature during stage III of FLASH [26].…”
Section: Introductionmentioning
confidence: 67%
“…The mechanisms that occur during flash are still under debate, although certainly, samples show a dramatic increase of both temperature and conductivity during the flash event and less dramatically, in a premonitory period before the onset of flash. The increase in conductivity is electronic in nature and the associated increase in sample temperature is attributed to Joule heating . What is unclear is whether additional changes in intrinsic properties of the material occur in response to the bias, leading to an enhanced Joule heating effect, rapid sintering, and associated luminescence; however, there continues to be a debate as to whether electroluminescence occurs or whether the observed luminescence is caused by black‐body radiation …”
Section: Introductionmentioning
confidence: 99%
“…The increase in conductivity is electronic in nature and the associated increase in sample temperature is attributed to Joule heating. 19,[23][24][25][26][27] What is unclear is whether additional changes in intrinsic properties of the material occur in response to the bias, leading to an enhanced Joule heating effect, rapid sintering, and associated luminescence; however, there continues to be a debate as to whether electroluminescence occurs 28 or whether the observed luminescence is caused by black-body radiation. 29 The aim of the present work was to investigate further the effect of both atmosphere and a small dc bias, simultaneously, on the electrical properties of 8YSZ.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum manufacturers for the aeronautical industry have invested in technology in order to make their product more competitive in the market compared to composite materials by improving the properties of aluminum and the quality of its production [1][2][3]. Al-Cu alloys of the 2000 series have their application in aircraft structures, mainly in the wings, as they present the excellent mechanical resistance obtained by heat treatment accompanied by good toughness [4][5][6].…”
Section: Introduction mentioning
confidence: 99%
“…The analysis of electrical conductivity was performed in real time using the four-terminal method during the heat treatment process and a correlation between hardness and aging times was stablished. This method is used in electronics to analyze the electrical resistivity of metallic materials [7][8][9], but it is little explored to monitor the behavior of electrical conductivity during artificial aging. During the monitoring and characterization of the 2024 alloy, analyses of hardness, electrical conductivity and material image were performed from samples as received, solubilized at 495 °C for 3 h, and with artificial aging treatment.…”
Section: Introduction mentioning
confidence: 99%